A human rights based approach to the global children's rights crisis: A call to action. (2nd November 2022) - Levy, Sheri R.; Migacheva, Katya; Ramírez, Luisa; Okorodudu, Corahann; Cook, Harold; Araujo‐Soares, Vera; Minescu, Anca; Livert, David; Ragin, Deborah Fish; Walker, Peter
Abstract: Children are not responsible for diseases, natural disasters, political conflicts, and wars; yet, children generally suffer the most. Although the UN Convention on the Rights of the Child (1989) is one of the most ratified world treaties, ample evidence of violations of children's rights exists in reports on the devastating effects of climate change, the COVID‐19 pandemic, and armed conflicts (e.g., Afghanistan, Haiti, Syria, Ukraine, Yemen) including abuse, abduction, becoming child soldiers, death, early marriages, family separation, loss of schooling, malnutrition, neglect, poverty, sexual violence, and trafficking, leading to traumatic short‐ and long‐term academic, emotional, psychological, and physical consequences. This article highlights a child‐rights based approach to the global crisis: (1) sounding an alarm for immediate and greater attention of governments to address children's rights violations and (2) calling multi‐disciplinary scholars to redouble their efforts toward freely sharing their findings, partnering with policy makers and stakeholders, collecting difficult to obtain data, and putting their knowledge into action in preventive and intervention measures to empower the implementation of children's protection and participation rights in the home, school, community, nation, and globally. The global multi‐faceted children's rights crisis requires urgent individual and collective action to make children's rights a global reality.